ESTIMATION OF SURFACE RUNOFF FOR AL-MAHALAH CATCHMENT'S USING SCS CURVE NUMBER METHOD AND GEOGRAPHIC INFORMATION SYSTEM TOOLS - Mazahreh, Safa; Mahasneh, Lubna Al; Ali, Aktar (International Journal of Research -GRANTHAALAYAH, 2018)
Natural resources and their sustainable management are key issues for the future development of national agricultural Strategy in Jordan. Similarly, vegetative cover, particularly rangelands, and its sustainable management are key concern in combating land degradation. The study area is located in the northern eastern area of Jordan and classified as Marginal area between with average annual rainfall less than 200mm. It suffers from land degradation due to overgrazing and mismanagement of vegetation cover, which has a substantial impact on the production system. Although it has a potential for water management. The main objective of this study is to estimate the runoff for Al-Mahalah watershed (using SCS Curve Number method) to construct an earth dam at suitable location in the watershed in order to harvest water for the benefit of local community and conserve soil. Data integration, analysis and processing for available and collected data were carried out in GIS environment. Runoff amounts were estimated at the watershed's outlet and the proposed location of an earth dam. The total amounts of runoff that could be derived from Al-Mahalah catchment's area at the catchment's outlet and an earth dam were estimated to be approximately 40000, 15000 m3, respectively.